Diary entry by Patricia Whiting, June 18 - Whiting, Patricia, 1940-2010:::Creator::::::::::::
Whiting describes a relationship with a man named Al. Based on correspondence in Series I from Carl D. Duncan in which he mentions the name Al, this entry was most likely written between 1964 and 1966.